Data Quality Automation: a Generic Approach for Large Linked Research Datasets - Muhammad A Elmessary; Daniel Thayer; Sarah Rees; Leticia ReesKemp; Arfon Rees (International Journal of Population Data Science, 2018)
Introduction When datasets are collected mainly for administrative rather than research purposes, data quality checks are necessary to ensure robust findings and to avoid biased results due to incomplete or inaccurate data.